PERFORMANCE LEVEL VARIATIONS IN MALE BASKETBALL PLAYERS: AN ANALYSIS OF PHYSICAL, PHYSIOLOGICAL, AND PSYCHOLOGICAL PROFILES - Kaushik, Neeraj; Dev Prakash (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The purpose of this study was to determine the effect of a 24 week training program on physical, physiological and psychological profiles for male national level basketball players. This research problem explores the primary research problem of how would the intervention affect the levels of anxiety, emotional intelligence, stress, mental health and concentration among the athletes. The controlled experimental design included 150 participants who were distributed into an experimental group receiving structured training and a control group maintaining their routine activities. In data collection, standardized psychological scales were used, while statistical analysis was performed using independent sample t test and repeated measures ANOVA. True to the findings, after training, the experimental group showed reduced anxiety and stress, increased emotional intelligence, increased concentration and mental health. Taken together these results suggest that targeted training of mental and physical capacities within athletic programs can boost directional resilience and cognitive performance to best realize overall sports performance. The study has important implications with respect to structured interventions to promote positive mental health among athletes and underscores the need for broader research in disparate populations and competitive levels.